A rare case of incarcerated femoral hernia containing small bowel and appendix. (9th August 2018) - Sinclair, Pierre; Kadhum, Murtaza; Bat-Ulzii Davidson, Tsetsegdemberel
Abstract : An 81-year-old woman was admitted under the acute medical team with a significant acute kidney injury secondary to presumed gastroenteritis, following a 5-day history of diarrhoea and vomiting. She continued to deteriorate despite resuscitative efforts. Subsequently, a non-contrast CT scan revealed likely small bowel obstruction second to a Richter's hernia in the inguinal canal. At diagnostic laparoscopy, both small bowel and appendix were identified to be incarcerated within the right femoral canal. The patient recovered uneventfully and was safely discharged several days following a laparoscopic appendicectomy and right femoral hernia repair.